O Programa Nacional de Integração da Educação Profissional com a Educação Básica na Modalidade de Educação de Jovens e Adultos – PROEJA: uma investigação acerca da concepção de currículo integrado dos professores que atuam nos cursos de secretariado e técnico administrativo em Cascavel - Lizzi , Maria Sandreana Salvador da Silva (2013)
This study has as object of analysis the implementation, Paraná Program National Integration in Education Professional with Basic Education in Modality of Education Youth and Adults – PROEJA, investigating the conception that teachers who work in courses Technical and Administrative Secretarial Staff in city of Cascavel have about Integrated Curriculum. The proposed objectives for the development of the research are: a) discuss the concept of Integrated Curriculum in official documents and national state regarding PROEJA b) study the concept of Integrated Curriculum, considering the work as a principle education and c) understand how to design integrated curriculum is understood by teachers. For the development of research, carried out the survey and analysis of documents implemented in national context leading PROEJA, such as: Law of Guidelines and Bases Education 9.394/96, Decree 2.208/97, Decree 5.154/04; documents regarding PROEJA: Base Document National (2006) and Guidance Document: Integrated Vocational Education Adult and Youth (2007). In addition to the official documents that deal with the PROEJA we made a literature review thesis and dissertations submitted a discussion on the subject. To conceptual and theoretical discussions about Integrated Curriculum, we take as a basis the productions of authors who discuss issue nationally, as well as propositions outlined by Marx and Gramsci. To understand the concept of teachers regarding curriculum Integrated conducted empirical research with teachers working in PROEJA in scope the Regional Education Center (NRE), Cascavel, in courses Technical and Administrative Secretarial Staff, belonging to the State School Teacher Francisco Lima da Silva, located in Forest district and State College Wilson Joffre, located in the city center. On first chapter, we present a historical context of the implementation education policy for schools Middle, Education and Professional Education Youth and Adults, which underlie development of thinking about integrated education and analyze educational policy produced at the national and state concerning this program: Base Document PROEJA (2006) of the Ministry of Education and the Guidance Document of the State of PROEJA Paraná titled Professional Education Integrated Education for Youth and Adults (2007). In the second chapter we made a literature review on the foundations of curriculum design integrated and a discussion of the concepts that underlie the proposal. Based on the analysis interview data, the third chapter presents the results of research empirical which is proposed to understand: which the conception that teachers teach courses in the PROEJA administrative and technical Secretarial Staff have Integrated Curriculum.